PENGGUNAAN KOSAKATA DAN TATABAHASA DALAM BERITA “VIRAL SUAMI SELINGKUH DENGAN IBU MERTUA, DIGEREBEK WARGA HINGGA ISTRI ALAMI TRAUMA” (ANALISIS WACANA KRITIS ROGER FOWLER) - Septian Gazali Rukmana; Agus Hamdani (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This study aims to describe the analysis of critical discourse in online news from Kompas.com December 2023 edition based on Roger Fowler's Theory. The data source for this research is a viral news article from Kompas.com online news with the title